Boron-induced oxygen vacancies for methanol oxidation reaction: selectivity towards formate via non-noble metals. Issue 15 (29th June 2022) - Naveen Kumar, T. R.; Swamynadhan, M.; Ghosh, Saurabh; Neppolian, B.
Abstract : Direct methanol fuel cells (DMFCs) with value-added product. Abstract : Bottlenecks in the commercialization of direct methanol fuel cells (DMFCs) involve the use of noble metal electrocatalysts, value-less by-product formation, and carbon dioxide (CO2 ) emission. Herein, we developed non-noble-based boron-doped nickel–cobalt oxide (B/NiCo2 O4 ) catalysts with abundant oxygen vacancies for efficient methanol oxidation to value-added formate as the by-product. The B/NiCo2 O4 catalyst demonstrated a maximum current density of ∼240 mA mg −1, which is 2.7 and 1.5 times higher than that of the pristine nickel–cobalt oxide (NiCo2 O4 ) and Pt/C (platinum on carbon) composite, respectively, accompanied with 1000 cycles stability. More excitingly, the value-added formate was produced as a by-product with a faradaic efficiency of 54%. The high current density and selectivity towards formate are mainly due to the accessibility of numerous methanol molecules on the B/NiCo2 O4 surface via B-doping induced oxygen vacancy formation. Moreover, the density functional theory (DFT) studies revealed that the strong binding of methanol on the B/NiCo2 O4 catalyst surface decreased the binding strength of intermediates and exhibited the tendency to prevent further oxidation reactions. This study provides new insights to develop cost-effective non-noble metal-based catalysts for methanol oxidation toward value-added by-product formation.